Mental health screening using the MINI test in medical students - León-Jiménez, Franco (2012)
Introduction: Mental health disorders are prevalent in higher education students and medical students are especially vulnerable. Objectives: To determine mental health problems frequency in students of Medicine. Design: Descriptive, transversal study. Setting: School of Medicine, Universidad Catolica Santo Toribio de Mogrovejo, Chiclayo, Lambayeque, Peru. Participants: Medical students. Interventions: During the 2010-I academic semester, frequency of mental health problems were determined using the Mini International Neuropsychiatric Interview (MINI) test, validated in Spanish, as a screening test for mental health. Main outcome measures: Frequency of mental health problems. Results: From 159 students interviewed, 94 were women (59,1%) and 65 men (40,8%). Average age was 18,7+/- 2,1 years; 35 students (22%) had at least one mental disorder. There were 16 (10,2%) students with history of hypomania episode, 11 with suicide risk (6,9%), 9 with current depressive disorder (5,6%), 8 with agoraphobia (4,8%), 8 with current anxiety disorder (4,8%); 20 (12,6%) and 11 (6,9%) students respectively mentioned that a health care provider had previously diagnosed anxiety and depression. Conclusions: Mental health disorders were frequent in these medical students; past hypomania episode, suicidal risk and current depressive disorder were the most frequently diagnosed mental health disorders.